Stromal scoring in advanced colon and rectal cancer: stroma-rich tumors and their association with aggressive phenotypes - Souza da Silva, Ricella; Queiroga, Eduardo; Osório, Cynthia; Cunha, Karin; Dias, Eliane (Archive of Oncology, 2021)
Background: Our aim was to explore relevance of the proportion between neoplastic cell component and tumor-associated stroma in order to assess its association with confirmed aggressive phenotypes of right/left colon and rectum cancers in a large series of patients. Methods: The quantification of stroma component was performed in patients diagnosed with colorectal adenocarcinoma who underwent surgical resection. The analyzed variables were age, gender, anatomical/pathological features, and tumor-stroma proportion. Tumor-stroma proportion was estimated based on slides used in routine pathology for determination of T status and was described as low, with a stromal percentage ≤50% or high, with a stromal percentage >50%. The tumor-stroma proportion was estimated by two observers, and the inter-observer agreement was assessed. Results: The sample included 390 colorectal adenocarcinoma patients. Stroma-rich tumors were observed in 53.3% of cases. Well-differentiated tumors had the lowest stromal proportions (p = 0.028). Stroma-poor tumors showed less depth of invasion (p
Keywords: Tumor microenvironment; Tumor-stroma proportion; colorectal cancer; advanced disease; aggressive phenotypes